Mediating Role of Mathematics and Science Engagement in the Relationship between Attitude toward STEM Education and Subjective Well-being of Adolescents - Kavitha Radha Nair; Jacqueline Kareem (Science Education International)
Science, technology, engineering, and mathematics (STEM) education has become a focal point of global discussions in the field of education. It emphasizes an interdisciplinary approach to learning. Subjective well-being of adolescents is characterized as joy to learn, close connectedness in schools, perception of the purpose of education, and the estimation of academic efficiency. This study investigates the mediating role of mathematics and science engagement in the relationship between the attitude toward STEM education and subjective well-being of school students in Kerala. Drawing upon theoretical frameworks from psychology, education, and sociology, this study employs a quantitative approach to data collection and analysis. A sample of 363 secondary and senior secondary students was administered standardized survey tools, measuring attitudes toward STEM education, subjective well-being, and their engagement in mathematics and science classes. Regression and mediation analyses resulted in indicating the positive, mediating effect of mathematics and science engagement in the relationship between the attitude toward STEM education and subjective well-being. Practically, the study suggests that educators should foster positive STEM attitudes through engaging teaching techniques and hands-on activities. Cultivating a positive STEM culture in schools can contribute to students’ well-being and equip them for future success in STEM fields.